Logo[s]terapi Eksistensial: Dialektika Logoterapi Viktor Frankl dan Konseling Pastoral - Belay, Yosep (Sekolah Tinggi Teologi Intheos Surakarta, 2025)
Abstract. Logotherapy is one of the third-generation counseling and psychotherapy models from the Vienna psychotherapy school. Viktor Emil Frankl developed the model with an existential analysis approach that emphasizes the spirituality of meaning as its foundation. Because his approach is quite